Targeting the source of fine sediment and associated geochemical elements by using novel fingerprinting methods in proglacial tropical highlands (Cordillera Blanca, Perú). Issue 8 (29th August 2022) - Navas, Ana; Lizaga, Iván; Santillán, Nelson; Gaspar, Leticia; Latorre, Borja; Dercon, Gerd
Abstract: In the Cordillera Blanca, the glaciers delineated by some of the highest peaks in the tropical Peruvian Andes have experienced a fast retreat over the last few decades. At the foot of Artesonraju Peak, the glacier‐fed river conveys fine sediments to Parón Lake, which is enclosed in the proglacial area created by the retreating glaciers of the unique confluence of the Huandoy, Chacraraju, Nevado Caraz and Artesonraju peaks (above 6000 m.a.s.l.). This research addresses the sediment contributions of main glacial landforms to sediment mixtures delivered to the river and lake system (1.6 km 2 ) by applying novel conservativeness and consistency methods for tracer selection and a frequentist unmixing model. A total of 27 surface soil and sediment sources (0–3 cm) were sampled from moraines, alluvial fans and recent colluvium, and 10 composite sediment mixtures, including suspended sediments, were collected to identify the sediment provenance. The unmixing results reveal large variability of the contributing sources related to their predominance and the locations of the mixtures. The largest contributions were from moraines, in percentages varying from 28% to as much as 77%. Alluvial fans contributed between 23% and 47% of the sediments, and colluvium material contributed the least, between 6% and 28%. At the time of sampling, ice melt discharge incising moraines and alluvial fans and eroding riverbanks were the main mechanisms of fine sediment delivery. Runoff over the bare surfaces of recently exposed moraines and the lack of vegetation cover in very active landforms also control sediment mobilization. Overall, highly dynamic changes in this paraglacial environment involve active sediment fluxes accompanying snow and ice melt. Our results indicate that in high tropical mountains, shrinking glaciers expose new surfaces of glacial materials, which deliver fine sediments. Identifying the contributing sources is of interest for water and sediment evaluation and management programs. Abstract : To identify the provenance of sediments in sediment mixtures collected in the proglacial area of Parón Lake we sampled main glacial landforms and apply innovative methods for guiding the selection of conservative and consensual tracers for unmixing. FingerPro model identifies moraines as the main contributing source, followed by alluvial fan and colluvium.